1985
DOI: 10.1523/jneurosci.05-11-03010.1985
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific opiate-binding sites occur in coated vesicles

Abstract: We prepared clathrin-coated vesicles from bovine forebrain utilizing sucrose or deuterium oxide-Ficoll density gradient centrifugation followed by permeation chromatography. Homogeneity was monitored by electron microscopy (EM) and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). EM revealed that the predominant (up to 98% of the total) organelles were coated vesicles and empty hexagonal baskets. Diameters of the coated vesicles ranged from 37 to 120 nm with a mean of 65.2 +/- 2.2. Upon SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Arrestin binding also promotes the targeting of desensitized receptors to clathrin-coated pits for their internalization (Ferguson, 2001). This well-documented targeting of GPCRs to the clathrin-coated pit/endosome pathway (Roth et al, 1981;Bennett et al, 1985;Chuang et al, 1986;von Zastrow and Kobilka, 1992) is critical because it allows for the resensitization and recycling of receptors (Yu et al, 1993;Pippig et al, 1995) and may be involved in down-regulation (Gray and Roth, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Arrestin binding also promotes the targeting of desensitized receptors to clathrin-coated pits for their internalization (Ferguson, 2001). This well-documented targeting of GPCRs to the clathrin-coated pit/endosome pathway (Roth et al, 1981;Bennett et al, 1985;Chuang et al, 1986;von Zastrow and Kobilka, 1992) is critical because it allows for the resensitization and recycling of receptors (Yu et al, 1993;Pippig et al, 1995) and may be involved in down-regulation (Gray and Roth, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…9-Adrenergic receptors have been reported to be present in coated vesicles and supposed to be inter nalized by the vesicles, resulting in desensi tization of this receptor on the plasma mem brane (4). In addition, muscarinic acetyl choline (5) and opioid receptors (6) were shown to be present in coated vesicles. a2 Adrenergic receptors (a2-receptors) are in volved in the control of a number of important physiological processes and suggested to relate to an etiology of depression (7,8).…”
mentioning
confidence: 99%
“…Because a redistribution of these receptors from the heavy to the light membrane fraction has been observed during desensitization, it was suggested that receptors in the light membrane fraction represent a population of desensitized receptors that are seques-tered away from the cell surface, probably by internalization Waldo et al, 1983;Sibley and Lefkowitz, 1985). For opioid receptors, Law et al ( 1984) have demonstrated internalization into endosomes after exposure of NG 108-15 cells to an opioid agonist, and Bennett et al (1985) found opioid receptor binding in clathrin-coated vesicles isolated from bovine brain. This can be taken as an indication that opioid receptors in the light membrane fraction are internalized receptors.…”
mentioning
confidence: 99%